Ion acoustic instability in dusty plasma - Susayev, Y.V.; Olshansky, V.V. (Вопросы атомной науки и техники, 2020)
The computer simulation results of the ion acoustic instability evolution in the dusty plasma are presented. The dusty plasma consists from electrons, ions, massive charged dust grains and neutral atoms. In the simulation the implicit PIC-code is used. To this code the implicit scheme of particles movement is applied, namely the direct implicit method of Langdon-Fridman. Realization of the algorithm is presented too.